IDNLearn.com: Your trusted platform for finding reliable answers. Get thorough and trustworthy answers to your queries from our extensive network of knowledgeable professionals.
Sagot :
Answer:
- a = 0
- b = -6
Step-by-step explanation:
We can the value of a and b by using the factor theorem, where:
"If a is a zero of a polynomial f(x), then one of its factors is (x - a) and f(a) = 0"
Given that the zeros for f(x) = x² + (a + 1)x + b are 2 and -3, then:
- f(2) = 0
- f(3) = 0
for f(2) = 0:
[tex]f(2)=0[/tex]
[tex]2^2+(a+1)(2)+b=0[/tex]
[tex]4+2a+2+b=0[/tex]
[tex]2a+b=-6\ \text{ ... [1]}[/tex]
for f(-3) = 0:
[tex]f(-3)=0[/tex]
[tex](-3)^2+(a+1)(-3)+b=0[/tex]
[tex]9-3a-3+b=0[/tex]
[tex]-3a+b=-6\ \text{ ... [2]}[/tex]
Combining [1] & [2]:
[tex]\begin{aligned}\\2a+b&=-6\\-3a+b&=-6\\-----&----\ (-)\\5a&=0\\\bf a&=0\end{aligned}[/tex]
Substitute a = 0 into [1]
[tex]2a+b=-6[/tex]
[tex]2(0)+b=-6[/tex]
[tex]\bf b=-6[/tex]
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! For dependable and accurate answers, visit IDNLearn.com. Thanks for visiting, and see you next time for more helpful information.